2009
DOI: 10.1080/13625180902925211
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender roles on health seeking behaviour during pregnancy in Turkey

Abstract: Providing information regarding the value of antenatal care also to elder women is essential in increasing the demand to the services. Incorporating gender perspectives into daily health practice and maintaining access to high quality reproductive care services are vital in reducing the gender based barriers to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…There are gender-based barriers that restrict women from leaving their homes for recreational activities. In Turkey, many decisions of women – even the decision of pregnancy – is generally in the domain of men due to patriarchal ideology ( 51 ) . This ideology is less pronounced in the West and Mediterranean than in the East, Middle and North ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…There are gender-based barriers that restrict women from leaving their homes for recreational activities. In Turkey, many decisions of women – even the decision of pregnancy – is generally in the domain of men due to patriarchal ideology ( 51 ) . This ideology is less pronounced in the West and Mediterranean than in the East, Middle and North ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted in Turkey indicated that cultural influences were linked to delay in seeking care when they experience complications and this was contributed by factors such as age, educational level, health insurance, getting antenatal care, family structure, and knowledge of the danger signs during pregnancy. This shows the impact of knowledge on health-seeking actions among pregnant women [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since care-seeking behaviour is not only an outcome of individual decision-making, it should be investigated in the community, taking into account its cultural, social and political environment. This indicates the need for qualitative research to gain an in-depth understanding of access-related factors in maternal care in Georgia [ 7 , 18 ].…”
Section: Introductionmentioning
confidence: 99%